Pengaruh Model Problem Based Learning (PBL) terhadap Kemampuan Literasi Sains Siswa dalam Pembelajaran IPA di Kelas V SD - Ariana, Safira Dwi; Putri, Hafiziani Eka; Rahayu, Puji (AS-SABIQUN, 2023)
This research was motivated by the low science literacy ability of elementary school students. This is because learning activities do not familiarize students with completing science literacy ability tests or problems related to science process skills. Efforts that can be made are to make students accustomed to solving problems with science process skills in learning activities, one of which is to use the Problem Based Learning (PBL) learning model. This study was conducted to determine the increase and effect of the application of the PBL model on students science literacy ability on heat transfer material in grade V for the 2022/2023 school year. To achieve this goal, a test in the form of a description containing indicators of science literacy ability is given to students. The research design used was a quasi-experimental research with a Nonequivalent Control Group Design design. The sample of this study was grade V students of SDN 4 Nagri Kaler consisting of 50 students divided into 25 students for the experimental group and 25 students for the control group. The conclusion obtained from the results of this study is that the increase in students science literacy skills using the PBL model is better than students who learn using conventional learning models and there is an influence of the application of the PBL model on students science literacy abilities. Students science literacy skills increased by 24.2% after being treated using the PBL model.